Hubungan Religiusitas dan Persahabatan dengan Kebahagiaan pada Mahasiswa Sekolah Tinggi Agama Islam Negeri Gajah Putih Takengon - Russy Ranggayoni; Abdul Munir; Cut Meutia (Tabularasa: Jurnal Ilmiah Magister Psikologi, 2020)
This research aim to know the correlation between religiosity and friendship with happiness on students. The proposed hypothesis is there a correlation between religiosity and friendship with happiness on students. This research was conducted to 100 students faculty of Islamic studies state Islamic high school. The methods used in this research is quantitative methods with the use of sampling techniques proportionate random sampling. The form of the scale in this research using a likert scale with a coefficient of reliability on the religiosity of 0,707, on the friendship of 0,740, and on happiness on students of 0,723. The analysis data used is analysis multiple regression and partial correlation. Based on the results of research it was concluded that there is a significant correlation between religiosity and friendship with happiness on students, indicated by the coefficient r = 0,686; with p = 0,00 means (p0,01) this means that the higher the religiosity and friendship then the higher the happinesson students. Based on the empirical mean and hypothetical mean of the religiosity variables in this research is (75.77055.00), the friendship variables is (78.02062.50) and the happiness on students variables is (75.06057.50) are known subject has high religiosity, friendship and happiness.